Tiger 17 and pexiganan as antimicrobial and hemostatic boosters of cellulose acetate-containing poly(vinyl alcohol) electrospun mats for potential wound care purposes - Teixeira, Marta Albertina (2022)
In this research, we propose to engineer a nanostructured mat that can simultaneously kill bacteria and promote an environment conducive to healing for prospective wound care. Polyvinyl alcohol (PVA) and cellulose acetate (CA) were combined at different polymer ratios (100/0, 90/10, 80/20% v/v), electrospun and crosslinked with glutaraldehyde vapor. Crosslinked fibers increased in diameter (from 194 to 278 nm), retaining their uniform structure. Fourier-transform infrared spectroscopy and thermal analyses proved the excellent miscibility between polymers. CA incorporation incremented the fibers swelling capacity and reduced the water vapor and air permeabilities of the mats, preventing the excessive drying of wounds. The antimicrobial peptide cys-pexiganan and the immunoregulatory peptide Tiger 17 were incorporated onto the mats via polyethylene glycol spacer (hydroxyl-PEG2-maleimide) and physisorbed, respectively. Time-kill kinetics evaluations revealed the mats effectiveness against Staphylococcus aureus and Pseudomonas aeruginosa. Tiger 17 played a major role in accelerating clotting of re-calcified plasma. Data reports for the first time the collaborative effect of pexiganan and Tiger 17 against bacterial infections and in boosting hemostasis. Cytocompatibility data verified the peptide-modified mats safety. Croslinked 90/10 PVA/CA mats were deemed the most promising combination due to their moderate hydrophilicity and permeabilities, swelling capacity, and high yields of peptide loading.